Morbidity and Mortality after High-dose Transfusion. (February 2016) - Johnson, Daniel J.; Scott, Andrew V.; Barodka, Viachaslau M.; Park, Sunhee; Wasey, Jack O.; Ness, Paul M.; Gniadek, Tom; Frank, Steven M.
Abstract : Background: It is well recognized that increased transfusion volumes are associated with increased morbidity and mortality, but dose–response relations between high- and very-high-dose transfusion and clinical outcomes have not been described previously. In this study, the authors assessed (1) the dose–response relation over a wide range of transfusion volumes for morbidity and mortality and (2) other clinical predictors of adverse outcomes. Methods: The authors retrospectively analyzed electronic medical records for 272, 592 medical and surgical patients (excluding those with hematologic malignancies), 3, 523 of whom received transfusion (10 or greater erythrocyte units throughout the hospital stay), to create dose–response curves for transfusion volumes and in-hospital morbidity and mortality. Prehospital comorbidities were assessed in a risk-adjusted manner to identify the correlation with clinical outcomes. Results: For patients receiving high- or very-high-dose transfusion, infections and thrombotic events were four to five times more prevalent than renal, respiratory, and ischemic events. Mortality increased linearly over the entire dose range, with a 10% increase for each 10 units of erythrocytes transfused and 50% mortality after 50 erythrocyte units. Independent predictors of mortality were transfusion dose (odds ratio [OR], 1.037; 95% CI, 1.029 to 1.044), the Charlson comorbidity index (OR, 1.209; 95% CI, 1.141 to 1.276), and a history of congestive heart failure (OR, 1.482; 95% CI, 1.062 to 2.063). Conclusions: Patients receiving high- or very-high-dose transfusion are at especially high risk for hospital-acquired infections and thrombotic events. Mortality increased linearly over the entire dose range and exceeded 50% after 50 erythrocyte units. Abstract : Mortality increased linearly with erythrocyte dose, reaching 50% in patients given more than 50 units of blood. Infection and thrombotic events were the most common complications.